2006
DOI: 10.1088/0305-4470/39/26/l03
|View full text |Cite
|
Sign up to set email alerts
|

First-order transitions for some generalizedXYmodels

Abstract: In this letter we demonstrate the occurrence of first-order transitions in temperature for some recently introduced generalized XY models, and also point out the connection between them and annealed site-diluted (lattice-gas) continuous-spin models.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 32 publications
2
17
1
8
Order By: Relevance
“…PR was further studied for =−3D / 4, where evidence of a first-order transition was found. The change of the nature of the phase transition from BKT to a discontinuous one agrees with previous RG predictions 23,24 and rigorous mathematical results; 22 on the other hand, in recent simulation studies of quenched dilution it was found that the transition temperature vanishes below the percolation threshold. [28][29][30][31] Notice that usage of the grand-canonical ensemble allows quite wide changes of density with temperature.…”
Section: Discussionsupporting
confidence: 88%
“…PR was further studied for =−3D / 4, where evidence of a first-order transition was found. The change of the nature of the phase transition from BKT to a discontinuous one agrees with previous RG predictions 23,24 and rigorous mathematical results; 22 on the other hand, in recent simulation studies of quenched dilution it was found that the transition temperature vanishes below the percolation threshold. [28][29][30][31] Notice that usage of the grand-canonical ensemble allows quite wide changes of density with temperature.…”
Section: Discussionsupporting
confidence: 88%
“…In turn, different techniques, such as self-consistent harmonic approximation (SCHA) and Monte Carlo (MC) simulation, have been used to study this transition when q > 1. It was found that the BKT critical temperature decreases as q increases and this model was proved to be the same universality class as the usual XY model [7,9,10,8]. Once the BKT transition appears, the vortex pair density starts to grow simultaneously.…”
Section: Introductionmentioning
confidence: 77%
“…would be an interesting question. Several methods mentioned in a number of the references may be helpful in finding a solution to this problem [7,8,[42][43][44].…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…͑2͔͒, and three-component spins which are coupled anisotropically. [28][29][30][31][32][33][34] A set of studies have put forward strong evidence that, although the introduction of vacancies does cause a region of first-order phase transitions to occur, it does not alter the Kosterlitz-Thouless ͑KT͒ critical behavior in other regions of parameter space. 35 In work on the phase diagram of three-dimensional systems, it has been argued that the elucidation of the properties of the VBCM is important to an understanding of experiments on 3 He-4 He mixtures confined between two walls.…”
Section: Introductionmentioning
confidence: 99%